Analisis Potensi Mesjid Sebagai Tempat Pertumbuhan Ekonomi Berbasis Ovop Di Kota Binjai - Adjie ahmad nugraha (Jurnal Ilmiah Ekonomi Islam, 2023)
The mosque is one of the most important things in Islam, where Muslims carry out many activities in the mosque starting from prayer to tadarus, but apart from being a place of worship to seek rewards, it is a strategic place and is always a place for worship selling at the mosque. can be a solution to develop the economy of the surrounding community. The purpose of this research is to see how the mosque's BKM makes programs to help the economy of the people around the mosque so that they become independent communities and this research uses qualitative research methods by means of observation where researchers conduct interviews with related parties starting from the management BKM to sellers who sell around the mosque.